Generalizing Pre-emption Right to other Bilateral Contracts - ÃšÂ¯Ã™ÂˆÃ˜Â¯Ã˜Â±Ã˜Â²Ã›ÂŒ, Ã˜Â³Ã›ÂŒÃ˜Â§Ã™ÂˆÃ˜Â´; Ã˜Â³Ã™Â„Ã˜Â·Ã˜Â§Ã™Â†Ã›ÂŒ, Ã˜Â¹Ã˜Â¨Ã˜Â§Ã˜Â³Ã˜Â¹Ã™Â„Ã›ÂŒ; Ã˜Â¹Ã™Â„Ã™Â…Ã›ÂŒ Ã˜Â³Ã™ÂˆÃ™Â„Ã˜Â§, Ã™Â…Ã˜ÂÃ™Â…Ã˜Â¯Ã˜Â±Ã˜Â¶Ã˜Â§; Ã™Â…Ã™ÂˆÃ˜Â³Ã™ÂˆÃ›ÂŒ Ã™Â†Ã˜Â³Ã˜Â¨, Ã˜Â³Ã›ÂŒÃ˜Â¯Ã˜Â¬Ã™Â„Ã˜Â§Ã™Â„ (Ø§ÙØªØ´Ø§Ø±Ø§Øª Ø¯Ø§ÙØ´Ú¯Ø§Ù ÙØ±Ø¯ÙØ³Û Ù Ø´ÙØ¯)
The right of pre-emption presented in jurisprudence and statutory law is one of the causes of acquisition and an object of Article 140 of Civil Law. One of the main conditions for acquiring the right of pre-emption, which most jurists and the Civil Law assert, is transferring the share by one shareholder through a sale contract. The paper, at first, mentions the main conditions needed for acquiring pre-emption right and presents different views regarding these terms, and then explores the supporting documents of the famous view. There are some indications such as: considering the justification mentioned for this right in hadiths, considering the Holy Legislatorâs (shÄriâ) definite aim for this right that is the denial of harm, and the necessity for right legislation and prevention of fraud; which would lead to the conclusion that pre-emption is a general right that could be extended to other bilateral contracts.